Intracellular acidification in neurons induced by ammonium depends on KCC2 function - Titz, Stefan; Hormuzdi, Sheriar; Lewen, Andrea; Monyer, Hannah; Misgeld, Ulrich (European journal of neuroscience, 2006)
The Cl--extruding neuron-specific K+-Cl- cotransporter KCC2, which establishes hyperpolarizing inhibition, can transport NH4+ instead of K+. It is, however, not clear whether KCC2 provides the only pathway for neuronal NH4+ uptake. We therefore investigated NH4+ uptake in cultured rat brain neurons. In neurons cultured for > 4 weeks, the response to NH4Cl applications (5 mm) consisted of an alkaline shift which reversed to an acid shift within seconds. Rebound acid shifts which followed brief applications of NH4Cl were blocked by furosemide (100 µm). They were rather insensitive to bumetanide (1 and 100 µm), in contrast to those induced in cultured glial cells. Rebound acid shifts persisted in the presence of 1 mm Ba2+ and in Na+-free solution but were inhibited by extracellular K+. In neurons with depolarizing GABA responses, indicating the absence of functional KCC2, applications of NH4Cl barely induced an acidosis. However, large rebound acid shifts occurred in neurons that had changed their GABA response from Ca2+ increases to Ca2+ decreases. Rebound acid shifts continued to increase even after the change in the GABA response had occurred and could be induced earlier in neurons transfected with KCC2 cDNA. We conclude that KCC2 provides the main pathway for fast neuronal NH4+ uptake. Therefore, NH4Cl-induced rebound acid shifts can be used to indicate the development of KCC2 function. Further, the well known up-regulation of KCC2 function during development has the inevitable consequence of opening a major pathway for NH4+ influx, which can be relevant under pathophysiological conditions.
Gesehen am 07.04.2021